A Study on Farmwomen Training Preference on Farm Implements - Shobhana Gupta; Shilpi Verma (Indian Journal of Extension Education, 2016)
The study was aimed at determining women farmers’ perception about importance, adequacy and need of training in farm implements. A sample size of 240 women farmers was taken for the study and analyzed. Simple random sampling technique was used for the sample selection and structured questionnaire was used to elicit information from the respondents. Both descriptive and inferential statistics were used for data analysis. The result showed highest information about the repair of pump sets, oil engine; electric motor etc. was most important and most needed. Exposure to the use of farm implements was perceived as most adequate. It can be inferred that the rural women are in need of training in majority of the areas in farm implements. Hence, there is a wide scope for the extension workers to organize and impart training to farm women in order to enhance their potential in adoption of improved technologies. Therefore, providing appropriate training in the area of farm implements to rural women will enable them in the updating their knowledge and enhancing in the skills.